Photodynamic ablation of early cancers of the stomach by means of mTHPC and laser irradiation: preliminary clinical experience. Issue 3 (1st September 1998) - Ell, C; Gossner, L; May, A; Schneider, H T; Hahn, E G; Stolte, M; Sroka, R
Abstract : Background —Radical surgical treatment has been the first choice for early gastric cancer, but high resolution endosonography allows in situ diagnosis with a high sensitivity and specifity and in consequence the option of local endoscopic treatment. Aims —To evaluate photodynamic therapy (PDT) using meso -tetrahydroxyphenylchlorin (mTHPC) as the photosensitiser in superficial gastric cancer. Methods —Twenty two patients with superficial early gastric cancer received mTHPC (0.075 mg/kg intravenously) and were treated 96 hours later with red light at 652 nm (20 J/cm 2 ). Tumour response was assessed by endoscopy and extensive biopsy. Results —Endoscopies performed two to three days after PDT showed a haemorrhagic fibrinoid necrosis of the mucosal layer. Complete remission was achieved in 16/22 (73%) patients: 13/16 (80%) with intestinal type cancer and 3/6 (50%) with a diffuse Lauren's carcinoma. The mean follow up period was 12 months and 20 months, respectively. An average of 1.8 treatment sessions was required. Severe side effects were not observed. Seven patients had mild to moderate skin photosensivity reactions; 12 had local pain after PDT for 1–10 days. Conclusion —PDT using mTHPC as the photosensitiser represents a safe and efficient method for topical treatment of early gastric cancer, especially of Lauren's intestinal carcinoma. If the preliminary results can be verified in larger patient series and during long term follow up, local treatment of early cancers of the stomach by PDT could be considered as a therapeutic option for selected patients.